Faktor Yang Mempengaruhi Tingkat Kepatuhan Pasien Terhadap Penggunaan Obat Antihipertensi Di Puskesmas Tarik Periode Maret-April 2023 - fita sari; Eko Yudha Prasetyo (Jurnal Farmasi Indonesia AFAMEDIS, 2023)
Hypertension or high blood pressure is an increase systolic blood pressure of more than 140 mmHg and diatolic blood pressure of more 90 mmHg on two measurement with an interval od five minutes in a state of sufficient rest. The succes of treatment in hypertension patient is influenced bye several factors, one of which is adherence to medication. Factors that influence the level of patient compliance include knowledge, motivation for treatment, and family support. The design of this study used a descriptive analytic with a cross sectional study approach, data collection was carried out by giving questionaires and conducting interviews to patient who met the criteria. The result showed that the factor that influenced the level of patient compliance were education, employment status, duration of suffering from hypertension, participation of health inscurance, level of knowledge, affordability of acces to health service, family support, and the role of health workers and motivation for treatment.